Association of Pediatric Cardiac Surgical Volume and Mortality After Cardiac ECMO. Issue 6 (November 2017) - Barrett, Cindy S.; Chan, Titus T.; Wilkes, Jacob; Bratton, Susan L.; Thiagarajan, Ravi R.
Abstract : Centers with higher surgical and extracorporeal membrane oxygenation (ECMO) volumes have improved survival for children undergoing pediatric cardiac surgery and ECMO, respectively. We examined the relationship between both cardiac surgical and cardiac ECMO volumes, with survival. Using data from the Pediatric Health Information System, we reviewed patients who underwent ECMO during the hospitalization for cardiac surgery or heart transplantation from January 2003 to June 2014. Among 106, 967 patients in 43 centers undergoing a Risk Adjustment for Congenital Heart Surgery-1 1–6 procedure (n = 104, 951) or cardiac transplantation (n = 2, 016), 2.9% (n = 3, 069) underwent ECMO support. Centers were categorized into volume quartiles based on annual ECMO and cardiac surgical volumes. Multivariable logistic regression models controlling for clustering by center and adjusting for factors associated with mortality were constructed. Although mortality was lower in ECMO centers that performed ≥7 ECMO runs (odds ratio [OR]: 0.44, 95% confidence interval [CI]: 0.22–0.88)] and centers performing ≥158 cardiac surgical cases (OR: 0.37, 95% CI: 0.22–0.63), surgical volume was more strongly associated with ECMO mortality. Centers with higher cardiac surgical volume had fewer ECMO complications. Cardiac surgical volume, compared with ECMO volume, is more strongly associated with cardiac ECMO survival. Abstract : Supplemental Digital Content is available in the text.